Letting Go of the Middle Years Programme: Three Schools' Rationales for Discontinuing an International Baccalaureate Program. Issue 1 (February 2020) - Dickson, Anisah; Perry, Laura B.; Ledger, Susan
International Baccalaureate Middle Years Programme (MYP) is recognized for its rigor, inquiry-based learning, and development of academic skills. While it is growing in popularity worldwide, some schools have discontinued the program. Literature on the reasons why schools discontinue the MYP is limited. Using a qualitative case study design, we examined the perspectives of school leaders, former MYP coordinators, and experienced MYP teachers at three private and public Australian schools to find out why they discontinued the MYP. Our findings add to the limited literature base on the topic—they reveal schools discontinued the program due to challenges from various systems-level constraints, leadership issues, school organizational structures, and individual teacher challenges. Although our small sample prevents generalizability, our findings generate novel insights and hypotheses that can inform school decision making and future research about the sustainability of the MYP.